2020
DOI: 10.3390/math8091407
|View full text |Cite
|
Sign up to set email alerts
|

Soil Temperature Estimation with Meteorological Parameters by Using Tree-Based Hybrid Data Mining Models

Abstract: The temperature of the soil at different depths is one of the most important factors used in different disciplines, such as hydrology, soil science, civil engineering, construction, geotechnology, ecology, meteorology, agriculture, and environmental studies. In addition to physical and spatial variables, meteorological elements are also effective in changing soil temperatures at different depths. The use of machine-learning models is increasing day by day in many complex and nonlinear branches of science. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
(36 reference statements)
1
12
0
1
Order By: Relevance
“…In The R 2 scores ranged between 0.73 and 0.92, NSE scores ranged between 0.66 and 0.91, RSR scores ranged between 0.30-0.58, PBIAS scores were within the limit (,+10), and MSE scores were reasonably low (∼ 2°C) during the validation periods, revealing high model reliability. The MAE scores for all the coastal cities ranged between 0.16-1.03°C pertaining to all models (Table 6), which are reasonable in comparison to earlier models of the Adaptive Neuro-Fuzzy Inference System (ANFIS) for predicting the ST approach by Mustafa et al (2020) (0.16°C); Support Vector Regression (SVR) approach for Global Solar Radiation (GSR) by Samadianfard et al (2019) (0.99°C); hybrid Decision Tree (DT), Gradient Boosted Trees (GBT) (DT-GBT) approach for predicting soil temperature by Sattari et al (2020) (0.52-0.97°C); Multilayer Perceptron (MLP) algorithm and SVR approach for predicting soil temperature by Shamshirband et al (2020) (0.72-5.17°C). The R 2 scores for all the coastal cities ranged between 0.73-0.92°C pertaining to all models (Table 6), which are reasonable in The LSTM-BiLSTM hybrid model was implemented using LSTM and BiLSTM with nine layers.…”
Section: Historical Trends Of Meteorological Variables Of Coastal Cities Of Indiasupporting
confidence: 72%
See 1 more Smart Citation
“…In The R 2 scores ranged between 0.73 and 0.92, NSE scores ranged between 0.66 and 0.91, RSR scores ranged between 0.30-0.58, PBIAS scores were within the limit (,+10), and MSE scores were reasonably low (∼ 2°C) during the validation periods, revealing high model reliability. The MAE scores for all the coastal cities ranged between 0.16-1.03°C pertaining to all models (Table 6), which are reasonable in comparison to earlier models of the Adaptive Neuro-Fuzzy Inference System (ANFIS) for predicting the ST approach by Mustafa et al (2020) (0.16°C); Support Vector Regression (SVR) approach for Global Solar Radiation (GSR) by Samadianfard et al (2019) (0.99°C); hybrid Decision Tree (DT), Gradient Boosted Trees (GBT) (DT-GBT) approach for predicting soil temperature by Sattari et al (2020) (0.52-0.97°C); Multilayer Perceptron (MLP) algorithm and SVR approach for predicting soil temperature by Shamshirband et al (2020) (0.72-5.17°C). The R 2 scores for all the coastal cities ranged between 0.73-0.92°C pertaining to all models (Table 6), which are reasonable in The LSTM-BiLSTM hybrid model was implemented using LSTM and BiLSTM with nine layers.…”
Section: Historical Trends Of Meteorological Variables Of Coastal Cities Of Indiasupporting
confidence: 72%
“…It only requires input to represent a data set containing many samples to train the algorithm. Recent studies showed the problems solved by the ML in various fields, such as hydrological and climatological applications (Samadianfard et al 2019;Sankaranarayanan et al 2019;Sattari et al 2020;Shamshirband et al 2020;Madhuri et al 2021;Sadeghfam et al 2021). ML techniques accurately and efficiently represented the unresolved problems in climate science results (Brenowitz & Bretherton 2018;O'Gorman & Dwyer 2018;Rasp et al 2018;Bolton & Zanna 2019;Salehipour & Peltier 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various advanced computational approaches have been applied in different fields such as chemical engineering [37][38][39][40][41][42][43][44], control and electrical engineering [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], pharmacy and medical science [60][61][62][63][64][65][66][67], industrial engineering [68,69], civil engineering [70][71][72][73], economic and business sciences, [74][75][76][77][78], mechanical engineering [79][80][81][82][83][84][85], energy engineering…”
Section: Mlp Neural Networkmentioning
confidence: 99%
“…Machine learning has recently received much attention in the soil temperature prediction field (Sattari et al 2020;Li et al 2020;Abyaneh et al 2016). It discovers significant underlying patterns in raw data by constructing a model without any human intervention.…”
Section: Introductionmentioning
confidence: 99%